2016
DOI: 10.1177/2325967116649901
|View full text |Cite
|
Sign up to set email alerts
|

Opening- and Closing-Wedge Distal Femoral Osteotomy

Abstract: Background:Lateral compartment osteoarthritis of the knee can be a challenging pathology in the younger, active population due to limited treatment options and high patient expectations. Distal femoral osteotomy (DFO) has been reported to be a potential treatment option.Purpose:To perform a systematic review on the survival, outcomes, and complications of DFO for treatment of genu valgum with concomitant lateral compartment osteoarthritis of the knee.Study Design:Systematic review; Level of evidence, 4.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 28 publications
(115 reference statements)
1
24
0
Order By: Relevance
“…Recently, a few systematic review articles have been published 31 , 32) . Saithna et al 32) included 6 case series and demonstrated poor reporting and heterogeneity among studies that precluded any statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a few systematic review articles have been published 31 , 32) . Saithna et al 32) included 6 case series and demonstrated poor reporting and heterogeneity among studies that precluded any statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, they concluded that DFO is a potential option for valgus osteoarthritis considering the long-term survivorship and good function. Chahla et al 31) performed a systematic review that included 14 studies. All were retrospective studies with good to excellent patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Minor complications such as stiffness and postoperative pain also appeared in both groups. The common complications were plate prominence, discomfort, or irritation over the plate [ 5 ]. Nonunion or hardware failure is a generally a concern during opening wedge DFO due to the opened gap.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, opening-wedge survival rate of 84%-100% was reported at 8-year follow-up. Hardware-related issues are the most prevalent complications of these surgical procedures [4,5].…”
Section: Introductionmentioning
confidence: 99%